An Evaluation the Suitability of the IT Infrastructure for Human Resource Flexibility at Tishreen University -A field study on workers at Tishreen University- (Journal of Hama University, 2020)
This research aims to determine the suitability of the information technology infrastructure for human resource flexibility at Tishreen University, by studying five dimensions of the information technology infrastructure (physical components, software, communication networks, databases, human resources). The researcher relied on the descriptive method, and he distributed a questionnaire to a random, accessible sample of workers (academics and administrators) at Tishreen University (100) workers.Based on the T-test for one sample using SPSS, the most important main result was: Tishreen University lacks to IT infrastructure Suitable for human resource flexibility from where of hardware, software, networks, and human resources, except for databases whose answers have been reasonably indicated by the answers of the research sample.       Then some recommendations were presented, the most important of which are: The necessity of working on providing communication networks between the departments of the same college, providing maintenance workers with skills and capabilities appropriate to the size and nature of work at the university, and providing software with sufficient flexibility to adjust it when needed.